Teaching in a pandemic: the transformation of teaching and clinical supervision (Canadian Medical Education Journal, 2021)
Introduction: The COVID-19 pandemic is an event that deeply impacts our personal, professional, and collective lives. How do we teach in these times of great upheaval? What are the main changes that have occurred?Method: Using the Cartel logic, four professors and a qualitative researcher carried out an autoethnographic research aimed at documenting the main changes that have occurred in the teaching of family medicine in their respective practices located in four different academic family medicine groups at the University of Sherbrooke.Results: Five key moments in teaching that occurred during a pandemic were identified: a) the declaration of a pandemic, b) the approach with the graduating/advanced cohort of residents, c) the anticipation and preparation for the arrival of new residents, d) arrival of first year residents and e) adaptation to the second wave. For each moment, we present the issues encountered in our care and teaching practices under three transversal relational axes: the relationship of humans to their cultural context, the patient-doctor relationship, and the teacher-resident relationship.Conclusion: Our analysis shows that the transmission of medical knowledge and the art of medicine cannot take place without specific attention to the overall cultural context, the contextual relationship of clinical care, and the teaching relationship. Our study also makes it possible to recommend the opening of spaces for reflection and dialogue in our teaching environments.